2018
DOI: 10.1016/j.devcel.2018.06.003
|View full text |Cite
|
Sign up to set email alerts
|

A Rapid Method for Directed Gene Knockout for Screening in G0 Zebrafish

Abstract: Zebrafish is a powerful model for forward genetics. Reverse genetic approaches are limited by the time required to generate stable mutant lines. We describe a system for gene knockout that consistently produces null phenotypes in G0 zebrafish. Yolk injection of sets of four CRISPR/Cas9 ribonucleoprotein complexes redundantly targeting a single gene recapitulated germline-transmitted knockout phenotypes in >90% of G0 embryos for each of 8 test genes. Early embryonic (6 hpf) and stable adult phenotypes were prod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
328
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(339 citation statements)
references
References 39 publications
(52 reference statements)
10
328
1
Order By: Relevance
“…Cortisol has high affinity both for Gr and Mr and they have been recently shown to be differentially involved in the regulation of stress axis activation and function in zebrafish (Faught and Vijayan, 2018), Therefore, we analysed the role of mr in the HIF response. To achieve this, we knocked-out mr in gr +/-;vhl +/-;phd3:eGFP incrossed derived embryos using CRISPant technology (Wu et al, 2018). Interestingly, phenotypic analysis performed on 5 dpf injected and uninjected larvae revealed that mr CRISPR injected vhl mutants were characterized by a significant downregulation of phd3:eGFP-related brightness at the level of the head (equals to 49%, P<0.0001), in the liver (equals to 56%, P<0.0001) and in the rest of the body (equals to 47%, P<0.0001), compared to vhl -/mutant uninjected larvae ( Fig.6a and 6b).…”
Section: Both Gr and Mr Are Directly Required For Assuring Proper Hifmentioning
confidence: 99%
“…Cortisol has high affinity both for Gr and Mr and they have been recently shown to be differentially involved in the regulation of stress axis activation and function in zebrafish (Faught and Vijayan, 2018), Therefore, we analysed the role of mr in the HIF response. To achieve this, we knocked-out mr in gr +/-;vhl +/-;phd3:eGFP incrossed derived embryos using CRISPant technology (Wu et al, 2018). Interestingly, phenotypic analysis performed on 5 dpf injected and uninjected larvae revealed that mr CRISPR injected vhl mutants were characterized by a significant downregulation of phd3:eGFP-related brightness at the level of the head (equals to 49%, P<0.0001), in the liver (equals to 56%, P<0.0001) and in the rest of the body (equals to 47%, P<0.0001), compared to vhl -/mutant uninjected larvae ( Fig.6a and 6b).…”
Section: Both Gr and Mr Are Directly Required For Assuring Proper Hifmentioning
confidence: 99%
“…In addition to structural damage sustained by the notochord due to targeted laser ablation, we wondered whether similar phenotypes can be observed by genetic perturbations. It has recently been reported that F0 CRISPR phenotypes concur with the ones observed in stable mutant lines (Wu et al 2018; Lischik et al 2018; Trubiroha et al 2018). We therefore decided to use the Tg (desmogon: EGFP) as a fast and straight-forward read-out of notochordal defects.…”
Section: Resultsmentioning
confidence: 53%
“…Making use of our newly generated transgenic line in combination with the recently published and publicly available single cell transcriptomics data from vertebrate embryos (Briggs et al 2018; Farrell et al 2018), we attempted to address this imbalance. To do so we performed a small scale F0 CRISPR screen, the efficacy of which has been recently demonstrated in Zebrafish (Wu et al 2018) and confirmed in other fish species (own observations and personal communications). Indeed, recent work in Medaka (Lischik et al 2018), in addition to our results from desmogon mutants, argues for the use of F0 injected embryos as a method to analyse tissue-specific phenotypes.…”
Section: Discussionmentioning
confidence: 98%
“…The wide range in efficiency of guide RNAs, however, increases the possibility of failure to detect phenotypes of interest due to inefficiency of guides (false negatives). Compensating for that by injecting multiple guides targeting the same gene carries the risk of increasing off-target effects (false-positives) (Shah et al, 2016;Tsai et al, 2015;Wu et al, 2018). Therefore, we reasoned that developing a pipeline that includes pre-screening of guide RNAs for high activity would allow us to inject fewer guide RNAs and only those that were highly active.…”
Section: Highlightsmentioning
confidence: 99%